MODEL TARIKAN DAN KARAKTERISTIK PERGERAKAN MENUJU TATA GUNA LAHAN PERGURUAN TINGGI DAN HUBUNGANNYA DENGAN PERKEMBANGAN WILAYAH IBUKOTA KABUPATEN KONAWE - Azis, Rudi (Universitas Halu Oleo, 2014)
Abstract???????????????There are four universities in the capital of Konawe (Unaaha) they are Lakidende University, College of Nursing (Nursing), Academy of Midwifery (AKBID) and College of Health Sciences (Stikes) Konawe. The existence of universities has appeal in side the primary needs of community, so that its presence has a positive impact towards development of Unaaha city.The objective of this research to produce a trip attraction model and know the characteristic of trip attraction toward college area in capital of Konawe. The results for each trip attraction model that produced in statistical models (regression) with a step by step of type 1 and for the characteristics use crosstab analysis (cross-classification).????????? The results for the trip atraction model toward college area in Konawe based regression test requires only one model that is Y = -1661.333 + 440667 X6, where variable X6 is totals of facilities. The results of chi-square analysis showed that the most dominant characteristic of trip attraction toward college area is the student movement who their home are located near from college area, and tend use motorcycles. Pattern of attraction also showed that the average student choose to live near campus and live in boarding house and some chose to stay at family home and rented house.?Keywords: Model, Trip attraction, Characteristics of trip attraction